Given that i = 1 ∑ 2 5 a i = 7 2 5 , where a 1 , a 2 , a 3 , … are in an arithmetic progression . Then find the value of r = 0 ∑ 1 2 a 2 r + 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a 1 + a 2 + . . . a 2 5 = 7 2 5 2 2 5 ( a 1 + a 2 5 = 7 2 5 a 1 + a 2 5 = 5 8
Now we have to calculate a 1 + a 3 + . . . + a 2 5 For this we can do ( a 1 + a 2 5 ) + ( a 3 + a 2 3 ) + . . . + ( a 1 1 + a 1 5 ) + a 1 3 Which can also be written as ( a 1 + a 2 5 ) + ( a 1 + a 2 5 ) + . . . + ( a 1 + a 2 5 ) + 2 ( a 1 + a 2 5 )
Which is 2 1 3 ( a 1 + a 2 5 ) = 2 1 3 5 8 = 3 7 7 So the correct answer is 3 7 7
In your sum in the problem, you ask to find a 3 + a 5 + ⋯ + a 2 5 , while in your solution you find a 1 + a 3 + ⋯ a 2 5 . I think that you meant to start from r = 0 .
Log in to reply
Yup I got it now from @cheo-Seong Cheong and hence edited the problem accordingly!!!
Problem Loading...
Note Loading...
Set Loading...
Let the first term and common difference be a = a 1 and d respectively. Then, we have:
i = 1 ∑ 2 5 a i = 2 2 5 ( 2 a + 2 4 d ) ⇒ a + 1 2 d = 7 2 5 = 2 9
Now we have:
r = 0 ∑ 1 2 a 2 r + 1 = a 1 + a 3 + a 5 + . . . + a 2 5 = a + ( a + 2 d ) + ( a + 4 d ) + . . . + ( a + 2 4 d ) = 1 3 a + 2 × 2 1 2 ( 1 2 + 1 ) d = 1 3 ( a + 1 2 d ) = 1 3 × 2 9 = 3 7 7